Gender Differences in Academic Performance of University Library and Information Science Students in Information Retrieval Course (2020-2025): An Ex-post Facto Study - Auwalu (Journal of Research in Industrial Technology and Educational Studies, 2026)
This study investigated gender-based differences in academic performance of university library and information science students in information retrieval course at Bayero University, Kano from 2020–2025. The specific objectives of the study were to determine gender distribution, compare mean performance, and test for statistical significance in achievement. Adopting an Ex-post Facto research design, the study utilized a census of 398 students (295 males, 103 females). Data were extracted from official departmental result sheets and analyzed using descriptive statistics and an Independent Samples T-test via SPSS. Findings revealed a male-dominated enrollment (74.1%), though female participation grew steadily to 32.8% by 2025. Descriptively, female students achieved a higher mean score (55.36) compared to males (51.37). The inferential analysis yielded a p-value of .008, indicating a statistically significant difference in favor of female students. These results challenge traditional stereotypes suggesting male superiority in technical ICT disciplines. The study concludes that while males dominate numerically, females demonstrate higher academic proficiency in technical IR competencies. The study recommended that include implementing outreach programs to encourage female enrollment in LIS, transitioning toward more practical-based laboratory sessions to elevate overall grade averages, and fostering gender-mixed peer support systems to enhance collaborative technical learning.